[An embracing moment] - Maria Isabel Contreras::::::photographer::: (2005)
Description supplied by photographer: 'Un momento de encuentro. Mi madre e hija regocijándose una con la otra durante su visita de Puerto Rico. Ya habián pasado 4 años desde que mi hija había visto a su abuela.' Translation of description: 'An embracing moment. My mother and daughter enjoying each others company during her visit from Puerto Rico. It ha[s] been 4 years since my daughter has seen her grandma.'